2019
DOI: 10.3390/genes10040261
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics in the Treatment of Cardiovascular Diseases and Its Current Progress Regarding Implementation in the Clinical Routine

Abstract: There is a special interest in the implementation of pharmacogenetics in clinical practice, although there are some barriers that are preventing this integration. A large part of these pharmacogenetic tests are focused on drugs used in oncology and psychiatry fields and for antiviral drugs. However, the scientific evidence is also high for other drugs used in other medical areas, for example, in cardiology. In this article, we discuss the evidence and guidelines currently available on pharmacogenetics for clop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 116 publications
0
16
0
Order By: Relevance
“…Nowadays, several attempts have focused on coumarins, as an abundant secondary metabolite, considered an effective bioactive molecule that present a promising therapeutic option. Coumarins are found in several plant families and essential oils and are used as fragrant additives in food and cosmetics [12]. Many reports have suggested that the coumarins possess a huge array of biological roles, such as antithrombotic, neuroprotective, antidiabetic, anticoagulant, anti-inflammatory, antioxidant, and antiplasmodial activities [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, several attempts have focused on coumarins, as an abundant secondary metabolite, considered an effective bioactive molecule that present a promising therapeutic option. Coumarins are found in several plant families and essential oils and are used as fragrant additives in food and cosmetics [12]. Many reports have suggested that the coumarins possess a huge array of biological roles, such as antithrombotic, neuroprotective, antidiabetic, anticoagulant, anti-inflammatory, antioxidant, and antiplasmodial activities [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Coumarins have a wide range of biological properties including antiviral, antimicrobial, anti-inflammatory, and other bioactivities. Some coumarins are approved for use in the treatment of various diseases [ 28 , 29 , 30 , 31 ]. The most important are vitamin K antagonists, such as warfarin, phenprocumone, or acenocumarol, which are used as anticoagulants [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cancer management, targeted therapy based on genetic data is widely applied (e.g., cetuximab for KRAS wild-type colorectal cancer, dabrafenib for cancers with V600E BRAF mutation). In cardiovascular disease, pharmacogenetic profiling for clopidogrel, warfarin, acenocoumarol, and simvastatin dosing is recommended [110,111]. At the same time, there are some obstacles that need to be overcome to fully implement pharmacogenetic testing in the clinical practice: we need robust evidence for cost effectiveness, physicians and patients need to be aware and trained, and commercial pharmacogenetic panels need to be developed [111].…”
Section: Discussionmentioning
confidence: 99%
“…In cardiovascular disease, pharmacogenetic profiling for clopidogrel, warfarin, acenocoumarol, and simvastatin dosing is recommended [110,111]. At the same time, there are some obstacles that need to be overcome to fully implement pharmacogenetic testing in the clinical practice: we need robust evidence for cost effectiveness, physicians and patients need to be aware and trained, and commercial pharmacogenetic panels need to be developed [111]. For IBD, to date, pharmacogenetic research has also produced the most success in the context of molecular patient profiling (e.g., TPMT and NUDT15 genetic testing in the context of thiopurine-induced myelotoxicity, Table 2).…”
Section: Discussionmentioning
confidence: 99%